Key criteria for choosing restaurants and food delivery scenarios in Moscow - D. A. Khokhlov; A. S. Brazhnikova (Вестник университета)
In a growing food delivery market, understanding consumer behaviour becomes a basic factor in the development of food delivery services. This study identifies criteria for selecting a restaurant by consumers and scenarios of ordering food delivery. The main purpose of the research is to define consumer objectives and behavioural scenarios of clients connected to services of ready and chilled meals delivery. Quantitative surveys and in-depth interviews were employed as research methods. The findings and conclusions were approved through test marketing campaigns. On the basis of the analysis results, three key consumer objectives were presented: “quick meal”, “pleasing oneself and loved ones”, and “feeding a company”. Also, various scenarios were high-lighted, according to which customers meet their consumer objectives under different conditions. In addition, two levels of criteria for selecting a restaurant were given: primary criteria that determine the restaurant’s compliance with the customer’s objectives, and secondary criteria that are used to choose the best option among suitable restaurants. The study not only expands the current understanding of consumer preferences and behavioural scenarios in the context of food delivery but also provides practical recommendations to optimise existing delivery services and to develop the new ones.